1997
DOI: 10.1021/ma970303m
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the Nature of the Active Species in the Polymerization of Methacrylates:  Inhibition of Methyl Methacrylate Homopolymerizations and Reactivity Ratios for Copolymerization of Methyl Methacrylate/n-Butyl Methacrylate in Classical Anionic, Alkyllithium/Trialkylaluminum-Initiated, Group Transfer Polymerization, Atom Transfer Radical Polymerization, Catalytic Chain Transfer, and Classical Free Radical Polymerization

Abstract: Reactivity ratios have been determined for the monomer pair methyl methacrylate and n-butyl methacrylate under a range of polymerization conditions. The value of using reactivity ratios as a mechanistic probe is discussed. Reactivity ratios determined where M1 = MMA and M2 = n-BMA are 1.04, 0.81, classical anionic; 1.10, 0.72 , alkyllithium/trialkylaluminum initiated; 1.76, 0.67, group transfer polymerization; 0.98, 1.26, atom transfer radical polymerization; 0.75, 0.98, catalytic chain transfer; and 0.93, 1.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
107
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 129 publications
(115 citation statements)
references
References 31 publications
7
107
1
Order By: Relevance
“…Similar observations have been made with other comonomer pairs. [20][21][22][23][24] Using NiBr 2 (PPh 3 ) 2 as catalyst, Moineau et al 31 recently reported similar reactivity ratios (r MMA ) 1.7; r nBuA ) 0.34).…”
Section: Resultsmentioning
confidence: 99%
“…Similar observations have been made with other comonomer pairs. [20][21][22][23][24] Using NiBr 2 (PPh 3 ) 2 as catalyst, Moineau et al 31 recently reported similar reactivity ratios (r MMA ) 1.7; r nBuA ) 0.34).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, there have been reports on the synthesis of gradient copolymers by ATRP. [9][10][11][12][13][14][15][16] Reactivity ratios and monomer infeed ratio play an important role in determining the structure of the copolymers. 17 In conventional radical polymerization, difference in the reactivity ratios of the monomers lead to variation of composition among the polymer chains.…”
Section: 2mentioning
confidence: 99%
“…Two methacrylate monomers during ATRP usually have comparable values of relative reactivity ratios, such as MMA and n-butyl methacrylate (r 1 ¼0.98 and r 2 ¼1.26, respectively) 28 or the methacrylate macromonomers of poly(ethylene oxide) and poly(3-hydroxybutyrate) (r 1 ¼0.89 and r 2 ¼1.12, respectively). 29 A similar effect was shown for the FRP of the comonomer pair MMA and AMA (r 1 ¼1.34 and r 2 ¼0.92, respectively); 17 when r 1 Br 2 , the random composition of the copolymer was postulated.…”
Section: Polymethacrylates With Anthryl and Carbazolyl Groups D Neugementioning
confidence: 99%